LEGAL CONSEQUENCES FOR MSME’S FOR NON-HALAL CERTIFIED FOOD AND BEVERAGE PRODUCTS (CASE STUDY OF MSMES IN PEKIRINGAN) - Hafidz Wahyudin; Yosvania Miranda; Ahmad Abdul Ghoni; Moh. Sigit Gunawan; Deni Yusup Permana (Jurnal Abdisci, 2024)
Halal food and beverage products are important, and business actors must protect consumers following the mandate of the Consumer Protection Law and the Halal Product Assurance Law. The government has issued a free halal certification policy until October 17, 2024. MSME actors must have it, one of which is for MSME actors in food and beverage products. Suppose they do not have a halal certificate until that date. In that case, MSME actors will be sanctioned by Government Regulation Number 39 of 2021 concerning implementing the Halal Product Assurance Sector. The author uses an empirical juridical research method by identifying the law, seeing the effectiveness of law enforcement in the community, and reviewing the legal consequences of its implementation, especially in the Pekiringan Village area, the economic center of Cirebon City. From the results of this study, the author obtained data that more MSME actors in food and beverage products in Pekiringan Village do not have halal certificates in distributing their products. Therefore, there will be legal consequences in the form of sanctions for MSME actors if they do not have a halal certificate until the date determined by the current regulations.